Changes In the Suggestion System as A Consequence of the COVID 19 Pandemic: A Study of an Automotive parts company in Poland - Łukasz WACŁAWIK (Communications of International Proceedings, 2025)
Covid-19 had a significant impact on human resources in the enterprise sector. Employees were forced to change their communication forms. Due to the Covid-19 pandemic, companies ceased using many solutions that required direct contact between employees. Such practices included submissions of improvement proposals. In this practice, employees suggest ides to improve their workstations. As a result, companies achieve savings especially through ideas that can be implemented in several workstations, which multiplies savings. The impact of Covid-19 on the human resources of manufacturing companies is obvious. Recently, there have been publications describing the course of the pandemic and its effects on the functioning of companies. There are definitely fewer studies that would analyze the changes that took place during the pandemic, particularly in the context of the use of such tools as employee suggestions. The research involved a review of the literature on the suggestion system that has been used in Poland since 1990s. Following the analysis of the literature, field research was conducted in a company in the automative sector. The research was conducted in the form of interviews both with shift managers and operators. The presented results were developed on the basis of internal company data; the generalizations were made based on the interviews. The Covid-19 pandemic significantly influenced the employee suggestion system. After many years of analyses, the necessity, i.e. the pandemic, transferred the employee suggestion system to databases. The research results confirm the growing importance of work digitalization that was already described by Amankwah-Amoah et al. (2021). Despite this, fewer submissions were not noticed. Moreover, computerization undoubtedly allows for a much easier analysis of employee suggestions at a company-, team, department- or individual employee scale. One should hope that this change should not lead to employee demotivation.
Keywords: Industry; suggestion system; motivation; COVID